2002
DOI: 10.1177/089686080202200310
|View full text |Cite
|
Sign up to set email alerts
|

Results of Peritoneal Equilibration Test during Treatment with Polyglucose Dialysis Solution

Abstract: Background Results of peritoneal equilibration test (PET) suggest prolonged effect of polyglucose dialysis solution (PG-DS) on peritoneal permeability. Objectives An evaluation of dialysate-to-plasma ratio (D/P) of urea, D/P creatinine, and D/D0 glucose (ratio of dialysate glucose at designated dwell time to dialysate glucose at 0 dwell time), and mass transfer area coefficients (KBD) of these solutes in PET before introduction, during administration, and after discontinuation of PG-DS in patients treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Stabilization of peritoneal transport rates was shown in CCPD patients with RRF using a daytime polyglucose exchange, but there was no statistically signifi cant difference from the patients who used standard solutions for the daytime exchange. 85,86 The prospective European Automated Peritoneal Dialysis Outcomes Study (EAPOS) showed that polyglucose solution slows the development of high peritoneal membrane permeability in anuric patients. 87 This study, however, was not randomized.…”
Section: Preservation Of the Peritoneal Membranementioning
confidence: 99%
“…Stabilization of peritoneal transport rates was shown in CCPD patients with RRF using a daytime polyglucose exchange, but there was no statistically signifi cant difference from the patients who used standard solutions for the daytime exchange. 85,86 The prospective European Automated Peritoneal Dialysis Outcomes Study (EAPOS) showed that polyglucose solution slows the development of high peritoneal membrane permeability in anuric patients. 87 This study, however, was not randomized.…”
Section: Preservation Of the Peritoneal Membranementioning
confidence: 99%
“…It was also shown with the use of PG DS. 19,20 However, in pa tients treated with cyclic continuous PD (CCPD), having still preserved residual renal function, peritoneal transport measured using the mass transfer area coefficient (MTAC) for urea, creati nine, uric acid and glucose, remained unchanged during 2 years followup and was not significant between the groups treated using the PG DS for daytime exchange and the group using glucose solution for daytime exchange. 21,22 Moreover, accompanied by higher peritonitis rate in the stan dard group compared to the bic group.…”
Section: Introductionmentioning
confidence: 99%